Upregulated miR-410 is linked to poor prognosis in colorectal cancer. Issue 3 (2nd July 2020) - Abedi, P; Bayat, A; Ghasemzadeh, S; Raad, M; Pashaiefar, H; Ahmadvand, M
ABSTRACT: Background: Although miR-410 acts as a cancer inducer in colorectal cancer, there is limited data on the clinical implications of miR-410 expression levels in patients. We hypothesized a link between miR-410 expression and its potential clinical values in patients with colorectal cancer. Material and methods: 120 colorectal cancer tissue specimens and 120 adjacent non-tumour tissues were obtained. Quantification of miR-410 expression levels was determined by, quantitative RT-PCR. Expression was analysed by clinical features. Results: miR-410 was up-regulated in malignant tissues compared with corresponding normal tissues ( P < 0.01), with TNM stage and lymph node metastasis ( P = 0.03, P = 0.004, respectively), and with worse overall survival ( P = 0.002). Multivariate survival analysis identified it as an independent risk factor for outcome ( P = 0.021, HR = 2.19; 95% CI = 1.12–4.25). Conclusion: Compared to normal non-cancerous tissues, miR-410 was overexpressed in tumour tissues and is independently associated with the unfavourable outcome. Levels of MiR-410 might a useful laboratory tool in managing and predicting the prognosis of colorectal cancer.